Comparative physiological and biochemical evaluation of salt and nickel tolerance mechanisms in two contrasting tomato genotypes. Issue 1 (18th March 2019) - Amjad, Muhammad; Ameen, Nuzhat; Murtaza, Behzad; Imran, Muhammad; Shahid, Muhammad; Abbas, Ghulam; Naeem, Muhammad A.; Jacobsen, Sven‐Erik
Abstract : Plant tolerance against a combination of abiotic stresses is a complex phenomenon, which involves various mechanisms. Physiological and biochemical analyses of salinity (NaCl) and nickel (Ni) tolerance in two contrasting tomato genotypes were performed in a hydroponics experiment. The tomato genotypes selected were proved to be tolerant (Naqeeb) and sensitive (Nadir) to both salinity and Ni stress in our previous experiment. The tomato genotypes were exposed to combinations of NaCl (0, 75 and 150 mM) and Ni (0, 15, and 20 mg l −1 ) for 28 days. The results revealed that the tolerant and sensitive tomato genotypes showed similar response to NaCl and Ni stress; however, the level of response was significantly different in both genotypes. The tolerant tomato genotype showed less reduction in growth than the sensitive genotype against both NaCl and Ni stress. Root and shoot ionic analysis showed a decrease in Na and increase in K concentration by increasing Ni levels in the growth medium. Moreover, accumulation of Na and Ni in tissues showed a decrease in membrane stability index and an increase in malondialdehyde contents. The activity of superoxide dismutase, catalase, peroxidase and glutathione reductase under NaCl and Ni stress was significantly higher in the tolerant compared to the sensitive genotype. Enhanced activity of many antioxidant enzymes in Naqeeb under stress conditions is among the other mechanisms that enabled the genotype to better detoxify reactive oxygen species and therefore Naqeeb tolerated the stresses better than Nadir.